2020
DOI: 10.1111/crj.13157
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes in oligometastatic non‐small‐cell lung cancer: A single‐centre experience

Abstract: BackgroundEven in oligometastatic stage 4 disease, survival rates are higher when curative approaches focus on both the primary tumour and metastasis. So, we aim to analyse our results of oligometastatic disease retrospectively.MethodsIn total, data on 52 non‐small‐cell lung cancer (NSCLC) patients with limited metastasis (one to three synchronous/metachronous) were retrospectively analysed. All treatment modalities associated with various treatment modalities [surgery, chemoradiotherapy (CRT), supportive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In this study, the 3‐ and 5‐year OS rates of 165 patients with lung metastases were 60.0% and 34.3%, respectively. The DFS rates were 39.4% and 23.7%, respectively, and the median survival time was 24.0 months, which was similar to those of previous studies 4–6,11 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, the 3‐ and 5‐year OS rates of 165 patients with lung metastases were 60.0% and 34.3%, respectively. The DFS rates were 39.4% and 23.7%, respectively, and the median survival time was 24.0 months, which was similar to those of previous studies 4–6,11 …”
Section: Discussionsupporting
confidence: 89%
“…If surgical intervention is selected in the stage of 'oligometastasis', patients may achieve 'cure' effect. [3][4][5][6]9 A retrospective study in Japan concluded that surgical treatment was superior to chemotherapy alone; after PM, the 5-and 10-year survival rates of patients with pulmonary metastases were 35-70% and 20-30%, respectively. However, the 5-year survival rate of patients treated with drugs alone is only 20%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study highlighted the possibility of long-term survival benefit in selected NSCLC patients with extra-cranial extra-adrenal oligometastases following metastatectomy. In line with the study, one original article also demonstrated the importance of nodal stage as a prognostic factor and the survival benefit of local ablative treatments in selected advanced-stage NSCLC patients with median OS of 35.2 months [ 135 ]. However, the efficacy of LCT for the treatment of NSCLC patients with liver oligometastases could not be drawn from the two studies due to relatively small sample size and various clinical outcomes.…”
Section: Liver Oligometastasesmentioning
confidence: 70%